Comparative Evaluation of Rice and Maize DDGS on Growth Performance and Blood Biochemical Parameters of Crossbred Heifers - Tomar, Abhisek S.; Baghel, Dileep S.; Agrawal, Himanshu; Parmar, Chirag P.; Lunagariya, Pravin M.; Vaghamashi, Dilip G.; Wadhwani, Kishan N. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted to evaluate the impact of feeding rice- and maize-based Distillers Dried Grains with Solubles (DDGS) on growth performance and blood profile of crossbred heifers. Eighteen crossbred heifers (75% Holstein Friesian × 25% Kankrej; Av. age 13.78±0.38 months, b.wt. 178.54±6.38 kg) were randomly allotted to three treatment groups: T1 (basal total mixed ration-TMR without DDGS), T2 (TMR with 10% rice DDGS), and T3 (TMR with 10% maize DDGS), and fed iso-nitrogenous and iso-caloric TMR, except DDGS. The experiment was carried out for 112 days under uniform management conditions. The results revealed no significant differences among treatments for body weight, daily body weight gain, indicating that inclusion of DDGS up to 10% supported normal growth. Haematological and serum biochemical parameters also remained within normal physiological ranges across all groups, indicating safe on health status. The findings demonstrate that both 10 % rice and maize DDGS can be safely incorporated in the diet of crossbred heifers as an alternative to conventional protein sources without compromising growth performance or blood health.